Pengembangan Media Pembelajaran Interaktif Editing Video Berbasis Adobe Flash - M, Maemunah; Mas'ud, Huzaima (Jurnal Ilmiah Multidisiplin Amsir, 2023)
In an effort to provide a quality and sustainable education, each study program needs to evaluate the Multimedia-based learning is an alternative learning that can be done in the classroom. Through based learning. In multimedia, the teacher can help lead students to get a learning situation in such a way as to provide a concrete understanding of the material presented. In this study, the development of interactive learning media for video editing based on Adobe Flash was carried out. The results of the study show that interactive learning animation simulations will deepen their understanding and increase their interest in editing. The results of the analysis also show that video editing learning media using the Adobe Flash application can be used as a support for online and offline learning to help students learn and see phenomena online.